Perbandingan Aktivitas Citizen Journalism dalam Media Massa Indonesia dan Korea Selatan: (Kajian Literature Review Pada Kompasiana dan Ohmynews) - Arifah, Arifah; Putri, Sekar (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Citizen Journalism is a journalistic activity that is no longer foreign in today's digital era. Becoming a citizen who is able to write news by prioritizing journalistic code of ethics and compliance with the code of ethics itself is not an easy thing to do, especially if the citizen does not have a background in communication science or journalism education. However, in reality there is still a lot of news content displayed by the mass media that comes purely from citizen writings, without going through the editing process. This seems to be considered trivial by certain media owners because the media gatekeeper function does not work and does not cross-check the citizen's writings, resulting in a lot of hoax news or misleading information. Through a qualitative descriptive literature review approach, this study aims to compare citizen journalism activities in mass media in Indonesia and South Korea. The focus of this study lies in the practice of citizen journalism in Kompasiana and Ohmynews. The results of this study found that hoax news was still found in Kompasiana written by citizens. Kompasiana does not carry out its gatekeeper function properly. The writings that appear in Kompasiana are entirely the responsibility of the author himself. This means that Kompasiana is not responsible for the content that is published. This of course causes the credibility of the media to decline. This is very different from the online media Ohmynews, a media from South Korea. Overall, the content in Ohmynews comes purely from the writings of its citizens. However, it is not easy for the media to publish it. Citizens must pass several strict selections required by Ohmynews. One of them is that they must follow the Ethic Code and Citizen Reporter Agreement so that their writings are published in the media. So it can be ascertained that the impact is to reduce hoax news and increase the credibility of the media. Therefore, the indicator of the achievement of the success of a mass media that carries out its educational function can be observed through the compliance of professional journalists and citizen journalists who prioritize the principles of the journalistic code of ethics.